2014
DOI: 10.1371/journal.pone.0089336
|View full text |Cite
|
Sign up to set email alerts
|

Two Non-target Recessive Genes Confer Resistance to the Anti-Oomycete Microtubule Inhibitor Zoxamide in Phytophthora capsici

Abstract: This study characterized isolates of P. capsici that had developed a novel mechanism of resistance to zoxamide, which altered the minimum inhibition concentration (MIC) but not the EC50. Molecular analysis revealed that the β-tubulin gene of the resistant isolates contained no mutations and was expressed at the same level as in zoxamide-sensitive isolates. This suggested that P. capsici had developed a novel non-target-site-based resistance to zoxamide. Analysis of the segregation ratio of zoxamide-resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…In oomycetes, zoxamide lab-induced resistance has also rarely been reported except in Pythium sylvaticum and P. capsici (Martinez et al 2003;Bi et al 2011). A difference between zoxamide and MBCs is that zoxamide is used against diploid-oomycetes whereas MBCs are used against haploid true fungi (Bi et al 2014). Zoxamide resistance selection risk was found to be low in laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oomycetes, zoxamide lab-induced resistance has also rarely been reported except in Pythium sylvaticum and P. capsici (Martinez et al 2003;Bi et al 2011). A difference between zoxamide and MBCs is that zoxamide is used against diploid-oomycetes whereas MBCs are used against haploid true fungi (Bi et al 2014). Zoxamide resistance selection risk was found to be low in laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations at codons 198 and 200 are commonly reported (Malandrakis et al 2011), and F200Y was also found responsible for high resistant (HR) phenotypes (Yarden and Katan 1993;Davidse and Ishii 1995). However, the situation was different for zoxamide Bi et al 2011;Malandrakis et al 2011;Bi et al 2014). Compared to the high frequency of MBCs resistant isolates, the frequency of Zox R isolates was low,which might be because the two fungicides are binding to different target sites of β-tubulin (Cai et al 2015).…”
mentioning
confidence: 98%
“…However, unlike zoxamide, benzimidazoles are only active against true fungi but not oomycetes. In addition, the resistance to benzimidazoles developed rapidly after their introduction 11 12 ; by contrast, resistance or reduced sensitivity to zoxamide has been rarely reported since it was commercialized in 2001 13 14 15 16 . Attempts to obtain isolates resistant to zoxamide in Phytophthora capsici and P. infestans with the use of chemical mutagenesis, UV irradiation, or adaptation have been largely unsuccessful 15 .…”
mentioning
confidence: 99%
“…However, the nucleotide sequence of the gene encoding the β-tubulin protein in these P. cactorum and P. capsici zoxamide-resistant isolates did not show any point mutations when compared with their parental wild-type isolates [2,3]. Sexual recombination studies have indicated that zoxamide resistance in P. capsici is controlled by two recessive genes [8]. In this study, proteomic analysis indicated that the mechanism by which the zoxamide sensitivity was decreased in P. cactorum is quite complex.…”
Section: Discussionmentioning
confidence: 99%
“…A further study suggested that zoxamide resistance is controlled by two recessive genes and that zoxamide resistance occurred when at least one pair of these alleles was homozygous. This result would imply that if sexual reproduction occurred in the same field, then the risk of pathogen resistance to zoxamide might be high [8].…”
Section: Introductionmentioning
confidence: 99%